Older People'S Preferences for Self-Involvement in Decision-Making if Faced With Serious Illness - Rafaela Jorge; Natália Calanzani; Adelaide Freitas; Rui Nunes; Liliana Sousa (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVES: To examine older people's preferences for self-involvement in end-of-life care decision-making in scenarios of mental capacity (competency) and incapacity, and to identify associated factors. METHODS: A cross-sectional survey was conducted including 400 individuals aged 60+ years living in the city of Belo Horizonte, Brazil. RESULTS: Among 400 respondents, 95.3% preferred self-involvement when capable (due to the high percentage, associated factors were not calculated) and 64.5% preferred self-involvement when incapable through, for example, a living will. Considering that participants could choose multiple answers, the most frequent combinations in the capacity scenario were "yourself" and "other relatives" (76.8%) and "yourself" and "the doctor" (67.8%). In the incapacity scenario, the most frequent combinations were "yourself" and "other relatives" (usually their children and, less often, their grandchildren) (59.3%) and "yourself" and "the doctor" (48.5%). Three factors were associated with a preference for self-involvement in an incapacity scenario. Those who were married or had a partner (widowed; adjusted odds ratio [AOR] = 0.37; 95% confidence interval [CI] 0.19-0.68) and those who were male (female; AOR = 0.62; 95%CI 0.38-1.00) were less likely to prefer self-involvement. Those who were younger, as in age bands 60-69 years (80+; AOR = 2.35; 95%CI 1.20-4.58) and 70-79 years (80+; AOR = 2.45; 95%CI 1.21-4.94), were more likely to prefer self-involvement. CONCLUSIONS: Most participants preferred self-involvement in both scenarios of capacity and incapacity. Preference for self-involvement was higher in the scenario of capacity, while preference for the involvement of other relatives (usually their children) was greater in the scenario of incapacity.